Hypoxia induces late preconditioning in the rat heart in vivo - Berger, Marc Moritz; Huhn-Wientgen, Ragnar; Oei, Gezina T.; Heinen, André; Winzer, Andreas; Bauer, Inge; Preckel, Benedikt; Weber, Nina Claudia; Schlack, Wolfgang; Hollmann, Markus W. (Anesthesiology, 2010)
Although hypoxic late preconditioning (LPC) limits ischemia-reperfusion injury in vitro, its cardioprotective effect is not established in vivo.In part 1, rats were exposed to 4 h of hypoxia (16%, 12%, 8% oxygen) before 24 h of reoxygenation. In part 2, normoxic rats received early preconditioning with sevoflurane (1 minimum alveolar concentration [MAC] for 3 × 5 min), continuous administration of 1 MAC sevoflurane, or 11 mg · kg · h propofol. Thereafter, all rats underwent 25 min of regional myocardial ischemia and 120 min of reperfusion. After reperfusion, hearts were excised for infarct staining. The expression of protein kinase C (PKC)α and PKCε was assessed by Western blot analysis and the expression of heme oxygenase-1 and vascular endothelial growth factor by reverse transcriptase polymerase chain reaction.In normoxic control rats, infarct size was 62 ± 6% of the area at risk. Hypoxic LPC reduced infarct size (LPC16: 36 ± 11%, LPC12: 38 ± 10%, LPC8: 39 ± 11%; each P < 0.001) to approximately the same magnitude as sevoflurane-preconditioning (40 ± 8%; P < 0.001). Combined LPC16 and sevoflurane preconditioning was not superior to either substance alone. Continuous sevoflurane or propofol was not protective. The PKC inhibitor calphostin C abolished the cardioprotective effects of LPC16. PKCε, but not PKCα, expression was increased 6 and 28 h after hypoxic LPC. Heme oxygenase-1 and vascular endothelial growth factor were transiently up-regulated after 6 h.Hypoxic LPC at 8%, 12%, and 16% oxygen reduces infarct size in the rat heart in vivo. This effect is as powerful as sevoflurane-preconditioning. PKCε is a key player in mediating hypoxic LPC.
Gesehen am 18.01.2023